Effect of polyamine metabolism inhibitors on Lewis lung carcinoma growth and metastasis - Samoilenko, О.А.; Milinevska, O.A.; Karnaushenko, O.V.; Shlyakhovenko, V.A.; Zaletok, S.P. (Experimental Oncology, 2015)
Aim:To study the influence of polyamine metabolism inhibitors on the growth, metastasis and ornithine decarboxylase (ODC) activity of Lewis lung carcinoma. Materials and Methods: Experiments were performed on female mice C57Bl/6 with Lewis lung carcinoma. Nω-hydroxy-nor-arginine (nor-NOHA) and α-difluoromethylornithine (DFMO) were used as arginase and ODC inhibitors, correspondently. Inhibition of tumor growth was calculated by comparison of tumor volume in the treated and control groups. The average number of metastases per animal in the group and the average volume of pulmonary metastases per animal in the group have been determined. Determination of ODC — the key enzyme of the polyamine synthesis — in the samples of experimental tumors was performed by method of Luqman S. Results: Administration of DFMO or it’s combination with nor-NOHA resulted in the decrease of tumor growth rate, number and volume of lung metastases and was accompanied with reduced ODC activity in tumor tissue. Сonclusion: Modifiers of polyamine metabolism may be considered as promising targeted cancer therapy. Key Words: Lewis lung carcinoma, metastases, polyamine metabolism, ornithine decarboxylase, α-difluoromethylornithine, Nωhydroxy-nor-arginine.